Enhancing Courtesy Ethics Among Grade VI Students Through Citizenship Education: A Case Study of State Elementary School Tamamaung 1, Makassar - Andi Agusniati; A Rizal; Burhan Burhan; Asdar Asdar; Nurwidyayanti Nurwidyayanti (STAI Hubbulwathan Duri, 2025)
This study explores how Citizenship Education (Civics) can improve students’ ethical politeness in sixth grade at Tamamaung 1 Makassar Elementary School. The research addresses concerns about declining student manners, especially in interactions with teachers and peers. A qualitative descriptive approach was applied to gain an in-depth understanding of student behavior and teacher strategies. Data were collected through classroom observations, interviews with teachers and students, and documentation, then analyzed narratively to identify themes of polite and impolite conduct. Findings show that teachers regularly encourage polite behavior such as respectful communication, attentive listening, and tolerance. Yet, some students still display impolite behavior influenced by family background and social environment. Teachers modeled good manners and applied classroom routines, including the “5S” culture (smile, greet, polite, friendly, courteous). However, politeness was not explicitly integrated into lesson plans, as curriculum guidelines lacked specific indicators. Despite this limitation, students generally responded positively, showing improvements in greetings, cooperation, and respect for peers’ opinions. The study concludes that Civics Education can foster ethical politeness when supported by consistent teacher modeling and reinforcement. Greater integration of character values into lesson planning is recommended to ensure sustained behavioral development in line with national education goals.